Pengaruh Rotasi Kerja, Promosi Jabatan, dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan KSPPS Tunas Artha Mandiri Nganjuk - Bram Septa Syailendra; Endah Kurniawati; Brahma Wahyu Kurniawan (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2023)
This study aims to determine the significance the effect of job rotation, promotion, physical work environment on employee performance. This type of research uses a quantitative approach. The sample of the research was KSPPS Tunas Artha Mandiri employees which are as many as 45 respondents. This study uses the Saturated Sampling Technique. The data collection technique uses a questionnaire that has been tested for validity and reliability first. The data analysis technique of this study uses the classical assumption test, as well as multiple linear regression tests. The results showed that the variables of job rotation, promotion, and physical work environment had a partial and simultaneous effect on the performance of KSPPS Tunas Artha Mandiri employees. In this study, the promotion variable has a dominant influence on employee performance, while the rest is influenced by other variables.